2021
DOI: 10.1111/opn.12378
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary medicines and lifestyle approaches by people living with dementia: Exploring experiences, motivations and attitudes

Abstract: Background Lack of effective treatments for chronic conditions is associated with high rates of complementary medicine (CM) use. However, little is known about CM use for dementia. Aims and Objectives The aim of this study was to explore the experiences, motivations, and attitudes towards CM use by people living with dementia in an Australian setting. Design This study had a qualitative research design; quantitative demographic information was also collected. Methods In‐depth interviews were conducted with peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Cultural competency has been established as a key strategy in reducing health care inequities and improving the quality of care for culturally and linguistically diverse populations (Steiner et al, 2021). For cultural competence to be effective, it needs to be more than just raising cultural awareness for existing services.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural competency has been established as a key strategy in reducing health care inequities and improving the quality of care for culturally and linguistically diverse populations (Steiner et al, 2021). For cultural competence to be effective, it needs to be more than just raising cultural awareness for existing services.…”
Section: Discussionmentioning
confidence: 99%
“…When the purpose is limited to dementia, the use rate is estimated to be 18.4%, but the frequency of CAM use remains high [ 25 ]. The use of CAM in dementia patients and their caregivers is widespread, and they have an overall positive perception of the use of CAM [ 26 ]. Moreover, a qualitative study conducted on the German elderly found that most participants welcomed the incorporation of CAM into their health care [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…acupuncture, massage) [10]. CMs are becoming more widely available and used by older adults, particularly herbal and nutritional medicines for the treatment of chronic health conditions including, cardiovascular disease [12], diabetes [13] and dementia [14,15]. Herbal medicines contain herbal substances or herbal preparations, with nutritional supplements/medicines containing vitamins, minerals and in combination formulas and herbal substances/preparations as well [11,16].…”
Section: Introductionmentioning
confidence: 99%